Forensic Dental Age Estimation Using Radicular Dentine Translucency in Indian (Himachal Pradesh) Population-A Digital Method - Akshay Sujith; Neeta Sharma; R Guru Prasad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Age estimation plays a crucial role in establishing identity of the individual. Root dentintranslucency (RDT) is one of the stable parameter and is based on the translucent zone present in the rootdue to calcific deposits.Aims & Objective: the aim of our study was to estimate age using root dentine translucency length in acluster of Himachal Pradesh (Indian Population) and to derive a population specific formula, also to observethe correlation between root dentine translucency and gender.Materials and Method:A digital calibration of translucency length was calculated in 80 extracted naturalteeth and was statistically analysed using Pearson’s correlation coefficient and regression model was appliedto derive the regression equation.Result: RDT length was positively correlated with chronological age with correlation coefficient r = 0.95,population specific regression equation was derivedAge (y) = 18.384 + 6.4654 x RDT and age was estimatedwith a mean absolute error of ±3.4 years.Discussion & Conclusion: This study reinforced the theory that RDT length is strongly correlated with age,a population specific linear regression equation was derived. However there were no significant differencesfor RDT and gender was observed.